Biomarkers of Osteoporosis: An Update - Parveen, Bushra; Parveen, Abida; Vohora, Divya (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Osteoporosis, characterized by compromised bone quality and strength is associated with bone fragility and fracture risk. Biomarkers are crucial for the diagnosis or prognosis of a disease as well as elucidating the mechanism of drug action and improve decision making. Objective: An exhaustive description of traditional markers including bone mineral density, vitamin D, alkaline phosphatase, along with potential markers such as microarchitectural determination, trabecular bone score, osteocalcin, etc. is provided in the current piece of work. This review provides insight into novel pathways such as the Wnt signaling pathway, neuro-osseous control, adipogenic hormonal imbalance, gut-bone axis, genetic markers and the role of inflammation that has been recently implicated in osteoporosis. Methods: We extensively reviewed articles from the following databases: PubMed, Medline and Science direct. The primary search was conducted using a combination of the following keywords: osteoporosis, bone, biomarkers, bone turnover markers, diagnosis, density, architecture, genetics, inflammation. Conclusion: Early diagnosis and intervention delay the development of disease and improve treatment outcome. Therefore, probing for novel biomarkers that are able to recognize people at high risk for developing osteoporosis is an effective way to improve the quality of life of patients and to understand the pathomechanism of the disease in a better way.
Keywords: inflammation